Responsibility and economics - Markus Beckmann; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2007)
Empirically, responsibility is a concept increasingly made use of in order to address societal issues. At the same time, it is a concept mainstream economics has, so far, hardly touched on. The paper shows that the application of economic reasoning to the responsibility concept can instruct a twofold learning process: First, the very tradition of economics allows to better understand and elaborate the semantics of responsibility. Here, the paper develops the concept of ordo-responsibility that differentiates between the initial basic game and the related meta-games. The focus thus shifts to the rule- setting processes and rule-finding discourses for which the actors can accept governance responsibility and discourse responsibility, respectively. Second, the rational-choice analysis of the responsibility concept also produces important insights for mainstream economic theory. Building on a simple model that delineates the responsibility aptitude of an actor, the paper explains why standard economics tends to attribute the rule-setting function exclusively to state actors. Yet, as the underlying nation-state paradigm depends on social determinants that are not universally given, such economic theory shows a double blind spot. Against this backdrop, the paper sketches out how to broaden the conventional perspective and identifies policy recommendations for state actors and business corporations.
urn:nbn:de:gbv:3:2-1174
Keywords: 330